Peningkatan Capacity Building Dalam Peningkatan Sadar Wisata di Desa Wisata Jembrak - Ray Octafian; Dyah Palupiningtyas; Andhi Supriyadi; Heri Usodo (Jurnal Pengabdian Masyarakat Waradin, 2022)
Jembrak Village has very diverse potentials that can be used as capital in developing as a Tourism Village. The following are the problems encountered in Jembrak Village, such as: (1) the need to form a Community-Based Local Management Agency to manage the tourism village potential in Jembrak Village; (2) it is necessary to train and increase the ability of community human resources to become the main actors in the management of Tourism Villages in Jembrak Village; (3) it is necessary to explore the unique tourism potentials of Jembrak Village to be presented to tourists as a local tourist attraction; (4) the participation of the Jembrak Village community in the framework of environmental management for the realization of sustainable tourism. The author succeeded in realizing programs to support the development of Jembrak Village as a Tourism Village. These programs are the Establishment of Jembrak Village Tourism Village Managers, Making Tista Village Tourism Village Brochures, Making Tista Village Tourism Village Brochures, Making Trekking Routes, Producing and Packaging Local Culinary for Jembrak Village, Making Jembrak Village Tourism Profile Books, Making Local Souvenirs.